2020
DOI: 10.1177/1477153520916515
|View full text |Cite
|
Sign up to set email alerts
|

Road lighting and distraction whilst driving: Establishing the significant types of distraction

Abstract: There is a body of research showing how changes in lighting conditions affect hazard detection in the context of driving after dark. There is a separate body of research showing that driving is impaired by distraction. The two have yet to be integrated: this is critical for lighting design recommendations because giving consideration to distraction may affect the optimal conditions established in lighting studies. A first step in that process is establishing the critical type(s) of distraction that might then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
(123 reference statements)
2
9
0
Order By: Relevance
“…It has been suggested that conversation is a critical distraction when driving 23 and the current results confirm that parallel distraction impairs the ability to detect peripheral targets. However, it is difficult to establish the Distraction and peripheral detection 15 degree of distraction imposed by conversation due to it being unstructured, emotionally involving, and needs to be tailored to each participant 27 and the nature of the conversation.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…It has been suggested that conversation is a critical distraction when driving 23 and the current results confirm that parallel distraction impairs the ability to detect peripheral targets. However, it is difficult to establish the Distraction and peripheral detection 15 degree of distraction imposed by conversation due to it being unstructured, emotionally involving, and needs to be tailored to each participant 27 and the nature of the conversation.…”
Section: Discussionsupporting
confidence: 82%
“…The 60 young participants were aged 18-25 years. This range is similar to that (17)(18)(19)(20)(21)(22)(23)(24) used by the (UK) Department for Transport to define young car drivers, for whom there is a high casualty rate when weighted by distance travelled. 44 One group of 30 completed the experiment using the simple response and the other group of 30 used the choice response.…”
Section: Participantssupporting
confidence: 67%
See 3 more Smart Citations